Міжнародно-правові стандарти права на доступ до публічної інформації - Аблякімова, Ельвіна Ернесівна; Аблякимова, Эльвина Эрнесовна; Abljakimova, Jel'vina (My University, 2013)
The article provides the review of the process of forming of the international legal rules that set up the right for access to the public information and the State’s obligations to provide the realization of those rights. The main principles of the legal regulation of these mutters are also determined.
Аблякімова Е. Е. Міжнародно-правові стандарти права на доступ до публічної інформації / Е. Е. Аблякімова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 130-138.
Keywords: формування міжнародно-правових норм щодо права на доступ до публічної інформації; обов’язки держави щодо забезпечення права доступу до інформації; доступ до публічної інформації; формирование международно-правовых норм по праву на доступ к публичной информации; обязательства государства по обеспечению права доступа к информации; доступ к публичной информации; the formation of international law on the right to access to public information; the State's obligation to ensure the right of access to information; access to public information